COMPARATIVE ANALYSIS OF TRANSPORT ACCESSIBILITY ASSESSMENT METHODS AND DEVELOPMENT OF AN INTEGRATED SYSTEM FOR THE NORTH KAZAKHSTAN REGION (Journal of Geography and Environmental Management, 2026)
This article adapts classical transport accessibility assessment methods to the specific characteristics of the road network in the North Kazakhstan Region, accounting for the significant remoteness of settlements from trunk routes. We contend that standard transport provision indicators offer only a superficial understanding of the regional situation. For the North Kazakhstan Region, it is critical to supplement these methods with an assessment of actual operational reliability. Consequently, a comparative analysis of domestic and international assessment methodologies was conducted, including gravity models and the cumulative opportunities method. Our findings indicate that existing frameworks provide an oversimplified picture, as they fail to account for region-specific risks—ranging from spring thaw to varying infrastructure potentials between small and support rural settlements.As a solution, we propose an integrated transport accessibility assessment system based on the synergy of Geographic Information Systems and gravity modeling tools. Unlike traditional approaches, the proposed model accounts not only for travel time but also for the availability of various services and economic opportunities. The results can be applied to regional transport infrastructure planning, specifically to justify investment priorities and enhance territorial connectivity. The proposed approach is aimed at reducing spatial disparities and increasing the overall efficiency of regional development
Keywords: transport accessibility; North Kazakhstan region; gravity model; integrated system; Geographic Information Systems